Effect of pre-partum supplementation of rumen protected methionine plus lysine and choline on the performance of crossbred cows - AMRUTKAR, S A; PAWAR, S P; THAKUR, S S; KEWALRAMANI, NEELAM; KAUR, JASMINE (The Indian Journal of Animal Sciences, 2016)
The study was conducted to determine rumen escape potential (REP) of commercial rumen protected methionine (RPM), lysine (RPL) and choline (RPC) products and to examine the effect of supplementing RPM plus RPL and RPC on the performance of preparturient crossbred cows. Crossbred cows (27; 2nd to 4th lactation) were randomly assigned to 3 groups of 9 animals each, on the basis of most probable production ability (MPPA). Cows in control group (T1), were fed basal diet as per NRC (2001). The cows in second group (T2), were supplemented with 5 g RPM and 20 g RPL, and those in third group (T3), were fed 54 g RPC per cow/day for 40 days pre-partum. In sacco study revealed that REP of RPM, RPL and RPC was 75.20, 54.97 and 72.89%, respectively. Supplementation of RPM plus RPL and RPC resulted in higher body condition score (BCS) in crossbred cows on the day of parturition. Nutrient intake was similar among the groups, except that duodenal supply of methionine and lysine was higher in T2 group. Plasma triglycerides, VLDL (very low density lipoproteins) and phosphatidylcholine levels were higher in T2 and T3 groups while vitamin E level was higher in T3 group, on the day of parturition, indicating better immune status. It was concluded that fortification of ration with RPM plus RPL and RPC resulted in improved body condition score, duodenal supply of methionine and lysine and better immune status in cows during prepartum period.